Comparative study of dinoprostone and misoprostol for induction of labor in patients with premature rupture of membranes after 35 weeks - Flavie Sire; Laure Ponthier; Jean-Luc Eyraud; Cyrille Catalan; Yves Aubard; Perrine Coste Mazeau (Scientific Reports, 2022)
Abstract The modalities of induction of labor in the event of premature rupture of membranes are controversial. The main purpose of this study was to compare the modalities of delivery after the use of dinoprostone or misoprostol for labor induction in the preterm rupture of membranes after 35 weeks in women with an unfavorable cervix. We then studied maternal and fetal morbidity for the two drugs. Retrospective, single-center, comparative cohort study in a level 3 maternity unit in France from 2009 to 2018 comparing vaginal administration of misoprostol 50 µg every six hours (maximum 150 µg) and administration of dinoprostone 10 mg, a slow-release vaginal insert, for 24 h (maximum 20 mg), for labor induction in the preterm rupture of membranes after 35 weeks in women with an unfavorable cervix (Bishop score < 6). We included 904 patients, 656 in the misoprostol group and 248 in the dinoprostone group. Vaginal delivery rate was significantly higher in the dinoprostone group (89% vs. 82%, p = 0.016). There were more cesarean sections for abnormal fetal heart rate in the misoprostol group (p = 0.005). The time interval from induction to the beginning of the active phase of labor and the duration of labor were shorter in the misoprostol group than in the dinoprostone group (437 min vs. 719 min, p < 0.001 and 335 min vs. 381 min, p = 0.0023, respectively). Maternal and neonatal outcomes were not significantly different in the two groups. Vaginal dinoprostone used for labor induction in preterm rupture of membranes seems to be more effective for vaginal delivery than vaginal misoprostol (50 µg).